PELATIHAN PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA KETEGAN, KECAMATAN TANGGULANGIN, KABUPATEN SIDOARJO - Ardhana Rahmayanti; Laily Noer Hamidah; Mokhammad Yahya (Universitas Nahdlatul Ulama Sidoarjo, 2020)
Waste has become a global problem. In Indonesia, the waste is transported to landfills (TPA) only 60-70%. Population growth causes an increase in the volume of waste due to increased consumption of the community. Waste if left will threaten the environment such as threats to climate change, air and water and soil pollution, loss of biodiversity, loss of resources and materials. Therefore, waste management is very important. Community involvement has become a key in handling waste. Reducing waste generation from homes with the 3R system and garbage has been considered to reduce waste and overcome the overflow of waste generation in the landfill. The Community Service Program in Ketegan Village, Tanggulangin Subdistrict, Sidoarjo Regency has been carried out to overcome the problem of garbage in the environment. Based on the situation analysis the steps used in overcoming the problem are in the form of training and ongoing assistance to the people of Ketegan Village. The method used is the delivery of material, demonstration of activities and discussion. The results show that Community Service activities can improve the understanding, attitudes and behavior of the Ketegan Village community towards waste management.